2007
DOI: 10.1128/jvi.02020-06
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Hepatitis B Virus Replication by the Regulatory X Protein In Vitro and In Vivo

Abstract: The 3.2-kb hepatitis B virus (HBV) genome encodes a single regulatory protein termed HBx. While multiple functions have been identified for HBx in cell culture, its role in virus replication remains undefined. In the present study, we combined an HBV plasmid-based replication assay with the hydrodynamic tail vein injection model to investigate the function(s) of HBx in vivo. Using a greater-than-unit-length HBV plasmid DNA construct (payw1.2) and a similar construct with a stop codon at position 7 of the HBx o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
177
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(208 citation statements)
references
References 24 publications
26
177
0
Order By: Relevance
“…The HBV regulatory protein HBx has been shown to potentiate viral replication in plasmid-based replication assays that use greater-than-unit-length HBV genomes transfected in HCC cell lines or injected via the mouse tail vein under hydrodynamic conditions (23)(24)(25)(26)(27). We have recently shown that transfection of plasmid free linear HBV DNA into Huh7 and HepG2 HCC cell lines (32) allows to fully recapitulate the HBV replication cycle, including the nuclear generation of viable cccDNA (30) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HBV regulatory protein HBx has been shown to potentiate viral replication in plasmid-based replication assays that use greater-than-unit-length HBV genomes transfected in HCC cell lines or injected via the mouse tail vein under hydrodynamic conditions (23)(24)(25)(26)(27). We have recently shown that transfection of plasmid free linear HBV DNA into Huh7 and HepG2 HCC cell lines (32) allows to fully recapitulate the HBV replication cycle, including the nuclear generation of viable cccDNA (30) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although initial studies suggested that HBx was not required for virus replication in cell culture (18), experiments with the highly related woodchuck hepatitis virus (WHV) system indicate that the WHV X protein (WHx) is required for virus replication in vivo (19)(20)(21)(22). Studies performed using a plasmid-based replication assays that use greater-than-unit-length HBV genomes transfected in HCC cell lines or injected via the mouse tail vein under hydrodynamic conditions have repeatedly confirmed that HBx potentiate HBV replication (23)(24)(25)(26)(27).…”
Section: H Epatitis B Virus (Hbv) Infection Is a Major Health Problemmentioning
confidence: 99%
“…It has been demonstrated that HBx transactivates the transcription of the major HBV genes, including HBcAg (4,18). Furthermore, some patients in the inactive viral replication phase of chronic hepatitis B infections do not express HBcAg in their liver (19), suggesting that the lack of HBcAg may contribute to HBV persistence.…”
Section: Discussionmentioning
confidence: 99%
“…From the 1 Institute of Cellular and Organismic Biology, Academia Sinica, Taipei, Taiwan; 2 Department of Pathology, Chang Gung Memorial Hospital, Keelung, Taiwan; 3 College of Medicine, Chang Gung Univeristy, Taoyuan, Taiwan; 4 Institute of Bioscience and Biotechnology, National Taiwan Ocean University, Keelung, Taiwan; 5 Institute of Fisheries Science, National Taiwan University, Taipei, Taiwan; 6 Institute of Microbiology and Biochemistry, National Taiwan University, Taipei, Taiwan; 7 Department of Aquaculture, and Center of Excellence for Marine Bioenvironment and Biotechnology, National Taiwan Ocean University, Keelung, Taiwan; 8 Division of Molecular and Developmental Biology, National Institute of Genetics, and Department of Genetics, Graduate University for Advanced Studies (SOKENDAI), Mishima, Shizuoka, Japan.…”
mentioning
confidence: 99%
“…7 HBV X (HBx) is a 16-kDa protein that has been implicated in the enhancement of viral replication, cell death, lipid metabolism, cell cycle regulation, DNA repair, and epigenetic modification. [8][9][10][11][12][13] HBx is frequently expressed in the tissues surrounding the tumor and may be involved in ICC formation. 14 It remains unclear whether the expression of HBx plays a functional role in the pathogenesis of ICC.…”
mentioning
confidence: 99%